POST-TRAUMATIC GROWTH PADA ANAK PEREMPUAN PASCA KEMATIAN AYAH - Stevie Feliana; Zakwan Adri (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Research on women’s experiences following paternal death in Indonesia remains limited, particularly studies that distinguish coping strategies, adaptation processes, and positive changes associated with post-traumatic growth. This study aimed to explore grief reactions and the resources perceived to help women adapt after the death of their fathers. A qualitative survey using an indigenous psychology approach was employed. The study involved 172 women who had lost their fathers due to death and were recruited through purposive sampling. Data were collected using an open-ended questionnaire and analyzed through thematic analysis. The findings showed that participants experienced various grief reactions, including sadness, a sense of loss, denial, anger, longing for their fathers’ presence, and gradual acceptance. Resources that supported the adaptation process included support from family and friends, spiritual practices and meaning-making, engagement in positive activities, emotional expression, and the development of independence. Some participants continued to experience difficulties in coping with the loss. These findings do not directly establish the occurrence of post-traumatic growth but identify adaptive resources and potential positive changes that require further investigation. The findings may provide a basis for developing bereavement support involving families, schools, religious communities, and mental health professionals. ABSTRAK Penelitian mengenai pengalaman perempuan setelah kematian ayah di Indonesia masih terbatas, terutama penelitian yang membedakan strategi koping, proses adaptasi, dan perubahan positif yang berkaitan dengan post-traumatic growth. Penelitian ini bertujuan mengeksplorasi reaksi duka dan sumber daya yang dipersepsikan membantu perempuan beradaptasi setelah kematian ayah. Penelitian menggunakan survei kualitatif dengan pendekatan indigenous psychology. Penelitian ini melibatkan 172 perempuan yang telah kehilangan ayah karena kematian dan direkrut secara purposif. Data dikumpulkan melalui kuesioner terbuka dan dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa partisipan mengalami beragam reaksi duka, seperti kesedihan, rasa kehilangan, penyangkalan, kemarahan, kerinduan terhadap keberadaan ayah, dan proses penerimaan. Sumber daya yang membantu proses adaptasi meliputi dukungan keluarga dan sahabat, praktik serta pemaknaan spiritual, keterlibatan dalam aktivitas positif, ekspresi emosi, dan pengembangan kemandirian. Sebagian partisipan juga masih mengalami kesulitan dalam menghadapi kehilangan. Temuan ini tidak secara langsung membuktikan terjadinya post-traumatic growth, tetapi mengidentifikasi sumber daya adaptasi dan kemungkinan perubahan positif yang perlu dikaji lebih mendalam. Hasil penelitian dapat menjadi dasar pengembangan dukungan kedukaan yang melibatkan keluarga, sekolah, komunitas keagamaan, dan tenaga kesehatan mental.